2023
DOI: 10.1002/ccd.30575
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technique on bifurcation stent outcomes in the European Bifurcation Club Left Main Coronary Trial

Abstract: Background Techniques for provisional and dual‐stent left main bifurcation stenting require optimization. Aim To identify technical variables influencing procedural outcomes and periprocedural myocardial infarction following left main bifurcation intervention. Methods Procedural and outcome data were analyzed in 438 patients from the per‐protocol cohort of the European Bifurcation Club Left Main Trial (EBC MAIN). These patients were randomized to the provisional strategy or a compatible dual‐stent extension (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…But based on current studies, routine pre-dilation of the SB is not recommended. Studies have identified the increased risk of SB dissection and subsequent challenges in rewiring the SB, ultimately resulting in adverse events [ 83 ]. However, it can be used when severe stenosis or angular lesions exist in the SB ostium resulting in impaired blood flow after the guidewire enters the SB.…”
Section: Stenting Strategy For Cblmentioning
confidence: 99%
“…But based on current studies, routine pre-dilation of the SB is not recommended. Studies have identified the increased risk of SB dissection and subsequent challenges in rewiring the SB, ultimately resulting in adverse events [ 83 ]. However, it can be used when severe stenosis or angular lesions exist in the SB ostium resulting in impaired blood flow after the guidewire enters the SB.…”
Section: Stenting Strategy For Cblmentioning
confidence: 99%